2012
DOI: 10.1002/mabi.201200170
|View full text |Cite|
|
Sign up to set email alerts
|

Human Elastin‐Based Recombinant Biopolymers Improve Mesenchymal Stem Cell Differentiation

Abstract: Elastin-based polypeptides are a class of smart biopolymers representing an important model in the design of biomaterials. The combination of biomimetic materials with cells that have great plasticity provides a promising strategy for the realization of highly engineered cell-based constructs for regenerative medicine and tissue repair applications. Two recombinant biopolymers inspired by human elastin are assessed as coating agents to prepare biomimetic surfaces for cell culture. These substrates are assayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…Additionally, the same study found ELP coatings on plastic and glass supported osteogenic differentiation of MSCs and high cell viability even in the absence of osteogenic media 108 . The surfaces of ELP based materials can be tuned at a nanometer scale to explore the in-depth effects of topography on cell behavior.…”
Section: Applications Of Mscs In Combination With Elastin-based Bimentioning
confidence: 76%
See 1 more Smart Citation
“…Additionally, the same study found ELP coatings on plastic and glass supported osteogenic differentiation of MSCs and high cell viability even in the absence of osteogenic media 108 . The surfaces of ELP based materials can be tuned at a nanometer scale to explore the in-depth effects of topography on cell behavior.…”
Section: Applications Of Mscs In Combination With Elastin-based Bimentioning
confidence: 76%
“…Recombinant ELPs modified with extra cross-linking sites to promote fibril formation have been demonstrated to enhance human bmMSC adhesion and proliferation in comparison to purely hydrophobic ELPs 108 . Additionally, the same study found ELP coatings on plastic and glass supported osteogenic differentiation of MSCs and high cell viability even in the absence of osteogenic media 108 .…”
Section: Applications Of Mscs In Combination With Elastin-based Bimentioning
confidence: 99%
“…Elastic protein (elastin) is a core protein of elastic fiber located in the pelvic floor extracellular matrix (ECM) [13]. Reduced synthesis and changes in the structure of elastin can promote the occurrence of POP.…”
Section: Wwwimpactjournalscom/oncotarget/ Oncotarget Advance Publimentioning
confidence: 99%
“…As far as their biological applications, HELPs have been widely investigated, in particular, for tissue engineering and regenerative medicine purposes, demonstrating for instance excellent biocompatibility with muscle [7] and stem [8] cells. Recombinant human peptides similar to ours were also proposed by other groups: recombinant versions of human tropoelastin were developed, used in the form of hydrogels and porous membranes and electrospun in elastomeric scaffolds, again for applications in tissue engineering and regenerative medicine [9,10].…”
Section: Human Elastin-like Polypeptidesmentioning
confidence: 99%